Respuesta :

The way to start a question like this is to write out a few of the recursive results. 

f(1) = - 3

f(2) = 3* f(n - 1) 
f(2) = 3 *f(2 - 1)
f(2) = 3 * - 3
f(2) = - 9

f3 = (3)*f(3 - 1)
f3 = (3)*f(2)
f3 = (3)*-9
f3 = - 27

Now you can go to the explicit function. You should notice that f(n) = 3^n in some form. Each current term is multiplied by 3.
 
F(1),F(2) and f(3) are all minus. Start with the minus first. It's probably a bit easier to understand.

They're all minus. No help there.

So the answer has to be fn = - (3)^n

Only B and D are choices. D won't work. Because the power is not (n - 1)
B <<<<< answer.